Development of conceptual framework for dyslexia learning aids / Siti Nur Solehah...[et al.] - Solehah, Siti Nur; Faaaizah, Wan Noor; Azizan, Hasnul Azwan; Shaharudin, Haszlin; Ahmad, Azrool (Universiti Teknologi MARA, Kedah, 2020)
In recent years, concern about dyslexia in child development has become an issue in Malaysia due to significant increase in numbers of children associated with this disability. It starts with an awareness on how important reading, writing and calculating are for our daily life. The skills mentioned are basic necessity to access and obtain knowledge. In addition, Malaysia has a long history of providing education for children with various categories of disabilities, especially in terms of primary and secondary education. This study intends to develop learning aids product in terms of providing better design for overcoming learning challenges and create learning effectiveness for this special group. Based on literature study and observation, this conceptual paper will discuss about the current product for dyslexia education and learning. The method for this research will use comparison data based on literature and existing product as analysis. As a result, this research has identified the development of conceptual framework for developing learning aids for dyslexia children.